Bond Market Developments and Service Delivery Paradoxes in Zimbabwean Local Government Institutions - Chilunjika, Alouis; Muswaka-Zinatsa, Phyllis; Intauno, Kudakwashe; Poshai, Leon; Muswaka, Charlene (Journal of Economic Development, Environment and People, 2024)
The creation of a functional bond market has emerged as a viable option to restore the financial vibrancy of local government institutions in Zimbabwe while, in the broad continuum, resolving the flagrant and gripping service delivery challenges encumbering the country’s local constituencies’ progress. In this regard, a qualitative desktop review was conducted. The study relied exclusively on purposively selected secondary documents. The study revealed that most local authorities in Zimbabwe are experiencing a liquidity crisis hence the development of a functional bond market will catalyse the alleviation of inflationary pressures and service delivery impasses that Zimbabwean local governments are grappling with. The study recommended that the bond market should be built on a strong foundation that includes political will and a stable currency regime to help create a conducive environment for the bond market while also mitigating the impact of the volatile political economy that currently exists in Zimbabwe.